Textures Recognition using Elman Neural Network - Fawziya Ramo; Alaa Mohamed (Al-Rafidain Journal of Computer Sciences and Mathematics)
In this research building system to recognition  texture images using artificial neural networks. The system consists of two phases: phase extraction important feature of each texture by using an algorithm Principal Components Analysis (PCA)   and recognition phase which recognize these feature by using  Elman network were trained network on a number of various texture  models down to the steady-state network  and then test the network by input  samples  of textures.  The experiments show that the method achieves high performance and produces 92% recognition rate.